Redescription and distribution of the rare flower chafer, Periphanesthes aurora (Motschulsky, 1858) (Coleoptera: Scarabaeidae: Cetoniinae) - Qiu, Jian-Yue; Xu, Hao; Chen, Li (Zootaxa, 2014)
This paper includes a detailed redescription of the monotypic genus Periphanesthes Kraatz, 1880 (Coleoptera: Scarabaeidae: Cetoniinae) and its type species, Periphanesthes aurora (Motschulsky, 1858), based on the lectotype (designated within) and additional specimens. Illustrations of external features and parameres are also provided. The distribution of P. aurora is studied, and its new distribution records are mapped. Bonsiella Ruter, 1965 is confirmed as a junior synonym of Periphanesthes Kraatz, 1880.